2018
DOI: 10.22175/mmb2017.11.0057
|View full text |Cite
|
Sign up to set email alerts
|

Processed Meat Thermal Processing Food Safety⁠—Generating D-Values for Salmonella, Listeria monocytogenes, and Escherichia coli.

Abstract: USDA, FSIS thermal processing guidelines (e.g. Appendix A for cooked beef, roast beef, and cooked corned beef, and Time-Temperature Tables for Cooking Ready-to-Eat Poultry Products) are widely used as validation support for cooking processes, but these procedures were developed and validated only for Salmonella in a limited number of products. To determine the extent to which Appendix A can safely be applied to other pathogens and products, a study was conducted to compare the thermal-death times of Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This indicates the effectiveness of heat treatment on the elimination of microbial in food. Wong et al (2011) researchers also reported similar findings which cooking treatment improved lethality on pathogens in ground beef (Guo et al, 2006;Yoon et al, 2013), egg (Fang and Huang, 2014), steak, hamburger or meat strips (Lahou et al, 2015), poultry-based meat products (Roccato et al, 2015), and processed meat (McMinn et al, 2018).…”
Section: Resultsmentioning
confidence: 67%
“…This indicates the effectiveness of heat treatment on the elimination of microbial in food. Wong et al (2011) researchers also reported similar findings which cooking treatment improved lethality on pathogens in ground beef (Guo et al, 2006;Yoon et al, 2013), egg (Fang and Huang, 2014), steak, hamburger or meat strips (Lahou et al, 2015), poultry-based meat products (Roccato et al, 2015), and processed meat (McMinn et al, 2018).…”
Section: Resultsmentioning
confidence: 67%
“…In previous study, the D-values at 60℃ of L. monocytogenes was 5.61 min (Murphy et al, 2004). The D-values at 65.6℃ and 71.1℃ of L. monocytogenes in uncured roast beef were 7.25 and 0.34 min, respectively, using water bath (McMinn et al, 2018). In another study, the resistance of five-strain L. monocytogenes cocktails was estimated in chicken breast piece and cooked in water bath.…”
Section: Determination Of D and Z-values For L Monocytogenes In Inoculated Restructured Goat Meat Cooked With Sous-vidementioning
confidence: 94%
“…However, one of the most heat resistant bacteria is L. monocytogenes. The D-value at same temperature of L. monocytogenes had higher than those of Salmonella and E. coli (McMinn et al, 2018). Thermal treatment times guidance and requirements for raw meat have been depended on the criterion and globally accepted parameters of heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Most published pathogen lethality studies use inoculated samples that have a high water activity (i.e., a w at >0.97) to measure the D-and z-values. In these studies, the inoculated meat samples are usually packaged in moisture-impermeable plastic film and then immersed in hot water for heating (O'Bryan et al, 2006;McMinn et al, 2018). As such, these experiments seldom account for the increased heat tolerance of desiccated pathogens resulting from surface dehydration that often occurs when products are cooked in forcedair convection ovens.…”
Section: Introductionmentioning
confidence: 99%
“…Cooking meat products in forced-air convection ovens such as impingement ovens is essentially a high-temperature drying process (Skjöldebrand, 1980). Based on previous research regarding drying phases during cooking, we hypothesized that during the wet-surface phases of a cooking process-the preheat and constant-rate drying periods-the inoculated Salmonella on the product surfaces would be fully hydrated and thus be susceptible to the standard D-and z-values from the literature for hydrated Salmonella (O' Bryan et al, 2006;McMinn et al, 2018). To test this hypothesis, we designed thermal processes for this study that used hydrated surface lethality (HSL) steps that exposed the product surfaces to lethal time-temperature conditions during the saturated-surface, constant-rate drying period.…”
Section: Introductionmentioning
confidence: 99%